PERLAKUAN AKUNTANSI TABUNGAN HAJI PADA BANK MEGA SYARIAH DI SURABAYA - Wahyuningsih, Ika; IMM, Nur Suci (The Indonesian Accounting Review, 2012)
This research aims to provide information about the management of savings hajj on syariahbanking and provides a description of the accounting treatment’s practice. Unit to be analyzedin this research is accounting treatment which includes the recognition, measurement,the presentation of, and disclosure over savings products with the principle mudharabah ofthe hajj saving on Mega’s syariah banking. Data collection method is direct observation,documentation, and interview. Criteria used in this research have met recognition of mudharabah,measurement of mudharabah, and presentation of mudharabah. Based on theanalysis, it is found that recognition was recognized in accordance of the nominal value orthe amount of money paid up capital of the company shall. The measurement was countedbased on the amount of money paid up capital of the company shall and calculation the ratioin accordance with the provisions of PT. Bank Mega Syariah. Savings of the hajj was servedin balance sheet and profit and loss statement. Savings of the hajj was expressed into savingsmudharabah.